LAHIRNYA SATU MASYARAKAT BARU MIGRASI DAN PERUBAHAN SOSIAL DI KALIMANTAN TIMUR SEPANJANG ABAD KE-20 - Dias Pradadimara (Populasi, 2001)
The flow of large number of migrants into Province of East Kalimantan has created a region known broadly as the province established by newcomers. As a discourse of indigenous and native vis-a-vis outsiders comes forth, the local government has better autonomy and authority to deciding the fate of its own territory. hue to an enormous number of migrants who have long been settled down in the area, it is exceedingly hard to determine who are considered as natives of East Kalimantan and who are the indigenous real Kutai.The ethnic Banjar in East Kalimantan has no longer continued practicing its specific traditional culture life. This, is similarly eventuated with the ethnic Java which has been separated from its native land is supposedly considered as 'Javanese". This circumstance is currently transpired in East Kalimantan, a process of recreation of what is considered influential in the context of social and political domain of a new society.